Business resilience and strategic responses in Ukraine and Lithuania during the Russia-Ukraine conflict: insights from the energy, agriculture, and manufacturing sectors - Uygur, Mehmet Recai; Peyravi, Bahman (Business: Theory and Practice, 2025)
This study examines the economic implications of Russia-Ukraine conflict has had on business operations in Ukraine and Lithuania. It seeks to examine how businesses have responded to the turmoil emanating from the conflict by breaking down disruptions in supply chains, regulatory adjustments as well as changes in market needs with specific reference to energy, agriculture and manufacturing sectors. The research will analyze secondary data from industry reports, financial disclosures and government sources. We chose this method so that we can evaluate what is presently there without the complexities and biases that come with collecting primary data using methods such as interviews. At the center of this dissertation lies unearthing patterns plus strategic insights that would inform businesses practices for similarly turbulent climates. Thus, it should be noted that the key thrust of this particular work is to extract strategies and tactical recommendations which could help keep firms resilient to geopolitical risks as well as exploit any arising advantages. The results are expected to be relevant for lawmakers, corporate executives, and economy planners thereby broadening their strategic frameworks on business operations within areas characterized by wars. This proposal is looking for funding support for comprehensive data analysis aimed at developing informed strategies that might considerably change sustainability and growth paths of enterprises both in Ukraine and Lithuania. Therefore, reliance on documented evidence alongside rigorous analysis of data will assist us in understanding how these economies operate in challenging contexts like these; providing essential knowledge required not only for theoretical debates but also suggesting ways towards enhancing economic resilience during times of geopolitical conflicts.